Eksperimen Pembelajaran Matematika Dengan Strategi Problem Based Learning (PBL) Dan Discovery Learning (DL) Terhadap Hasil Belajar Ditinjau Dari Kemampuan Berpikir Kreatif Siswa Kelas VIII Semester Genap Di Mts Negeri Surakarta II Tahun 2015/2016 - NUR AINI, MAY SYARAH (2016)
This research aims to determine: (1) the effect of learning Problem Based Learning (PBL) strategy and Discovery Learning (DL) strategy for mathematics learning outcome, (2) the effect of the level of creative thinking ability for mathematics achievement, (3) the interaction between learning strategy and creative thinking ability for mathematics learning outcome. The type of the research is experiment with quasi experimental design. The population of the research was all students of VIII Grade of MTs N Surakarta II of even semester of academic year 2015/2016. The research sample consisted of two classes. The sampling technique use cluster random sampling. Methods of data collection use test and documentation. Methods of data collection use test and documentation. Data analyzed by analysis of variance with two different cell lines with a significance level of 5%. Based on hypothesis testing, we concluded that: (1) there is effect of Problem Based Learning of strategy and Discovery Learning strategy for mathematics learning outcome, (2) there is effect of the level of creative thinking ability for mathematics learning outcome, (3) there is no interaction between Problem Based Learning strategy and Discovery Learning strategy based with creative thinking ability creative thinking ability for mathematics learning outcome.